2017
DOI: 10.1055/s-0037-1605382
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Neck Fractures Associated with Distal Radius Fractures

Abstract: There is little published data to guide management of ulnar neck fractures associated with fractures of the distal radius. As unplanned surgery usually reflects adverse events and this injury combination is relatively uncommon, we used a large database to study the incidence of unplanned surgeries after surgical and nonsurgical treatment of distal metaphyseal ulna fractures associated with a distal radius fracture and identify factors associated with these unplanned surgeries. We identified 277 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several studies have shown the validity of conservative treatment. 12 - 17 Namba et al described a technique wherein the distal radial fractures were securely fixed with a palmar plate, leaving the associated ulnar fractures unfixed. 12 Fourteen patients with a mean age of 74 years were treated and followed up at approximately 18 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown the validity of conservative treatment. 12 - 17 Namba et al described a technique wherein the distal radial fractures were securely fixed with a palmar plate, leaving the associated ulnar fractures unfixed. 12 Fourteen patients with a mean age of 74 years were treated and followed up at approximately 18 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Özkan et al reviewed the management of ulnar neck fractures associated with fractures of the distal radius. 15 They used a large database to study the incidence of unplanned surgeries after surgical and nonsurgical treatment of distal metaphyseal ulnar fractures associated with a distal radius fracture and identified factors associated with these unplanned surgeries. They identified 277 patients with an ulnar neck fracture associated with a distal radius fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies comparing conservative and surgical treatment of a concomitant ulnar fracture in patients treated with plate fixation for a displaced DRF suggest there are no differences in clinical and patient-reported outcome 21-23 . In addition, patients treated surgically for both fractures may have more subsequent unplanned surgeries compared with patients in whom the USF was left untreated 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Özkan and colleagues performed a database study where younger age, open fracture, multi-fragment fractures, and initial open treatment of ulnar neck fractures were shown to be associated with additional unplanned surgery, used as a measure of adverse events of fracture treatment (Ozkan, Fischerauer et al 2018). A retrospective study on 48 isolated distal ulna fractures showed no difference in healing time regardless of whether the fracture was surgically treated or not.…”
Section: Figure 10 Different Methods Of Internal Fixationmentioning
confidence: 99%